Pengaruh Kapitalisasi Pasar pada Manajemen Laba dengan Dewan Komisaris Independen dan Kualitas Auditor Sebagai Pemoderasi - Puspitasari, Ida Ayu Widya; RM, Ketut Muliartha (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p10, 2018)
Management performance based on profit tends to pay more attention on earning profit. it makes management can do earnings management as a result of agency problems. The driving factor of earnings management is market capitalization. Improvements on company management such as independent board of commissioners and auditor quality are necessary to suppress such earnings management.The sample of this research are property and real estate sub sector in Indonesia Stock Exchange period 2012-2016 based on purposive sampling method with total 126 observation. Data collection obtained by non participant observation method. Analysis method in this research is Moderated Regression Analysis.The results of the analysis shows that market capitalization has no effect on earnings management. Furthermore, independent board of commissioners and auditor quality is not able to moderate the relationship. It shows that size of market capitalization and application of internal and external controls do not affect the occurrence of earnings management. Keywords: Earning management, market capitalization, independent board, auditor quality